Fabrication and properties of the thickness mode ultrasonic transducer based on 0.15Pb(Mg1/3Nb2/3)O3-0.38PbHfO3-0.47PbTiO3 piezoelectric ceramics. Issue 8 (1st June 2020) - Wang, Jushan; Xiao, Junjie; Zhao, Xiangyong; Wang, Feifei; Tang, Yanxue; Zhang, Qiaozhen; Fang, Bijun; Zhu, Rongfeng; Yue, Qingwen; Liu, Dongxu; Deng, Ji
Abstract: In this paper, the 0.15Pb(Mg1/3 Nb2/3 )O3 -0.38PbHfO3 -0.47PbTiO3 ternary piezoelectric ceramic fabricated by the partial oxalate method that exhibits superior electrical properties ( d 33  = 447 pC/N and k t  = 56.9%) and excellent thermal stability of the piezoelectric properties below T C was studied. The newly discovered piezoelectric ceramic had a high Curie temperature ( T m  = 297 °C), this feature was used to fabricate a novel single-element ultrasonic transducer whose center frequency was 2.15 MHz, with a −6 dB bandwidth of up to 79.07%, and a sensitivity that reached −31.75 dB. The result of the experiment agreed well with that of PiezoCAD software based on the KLM model. This transducer's outstanding thermal stability below T C can be widely used in non-destructive evaluation. At the same time, we measured the sound field distribution of the ultrasonic transducer. The focal length was measured approximately 47 mm. An obvious main lobe was clearly seen from the z–x scan. The power was measured as 17.98 mW; the beam width of –3dB was 3.5 × 3.6 mm; and the area was 9.83 mm 2 according to the FDA and IEC standards.